High Harmonic Generation in Quantum Dots in Short Pulse - Lahon, Siddhartha; Mohan, Man (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
We consider high harmonic generation from a quantum dot (QD) in the presence of chirped laser pulse. The system dynamics is described by coupled equations which are solved numerically for various material parameters of QD and external laser field. Results show the effective controlling effect on the generation of High Harmonic Generation by changing the Chirping parameter of the laser pulse and the size of the QD which otherwise is not possible in other systems.